2021
DOI: 10.3389/fendo.2021.688071
|View full text |Cite|
|
Sign up to set email alerts
|

ACE Gene Variants Rise the Risk of Severe COVID-19 in Patients With Hypertension, Dyslipidemia or Diabetes: A Spanish Pilot Study

Abstract: Coronavirus disease 19 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection continues to scale and threaten human health and public safety. It is essential to identify those risk factors that lead to a poor prognosis of the disease. A predisposing host genetic background could be one of these factors that explain the interindividual variability to COVID-19 severity. Thus, we have studied whether the rs4341 and rs4343 polymorphisms of the angiotensin converting enzyme … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“… ( Gunal et al, 2021 ) ACE rs4341, rs4343 Spain 128 COVID-19 patients rs4341 and rs4343 were associated with more severe SARS-CoV-2 disease in patients with hypertension and diabetes. ( Íñiguez et al, 2021 ) ACE, ACE2 rs2106809,rs2285666 Turkey 155 COVID-19 patients No association was observed with the severity of SARS-CoV-2 infection. ( Karakaş Çelik et al, 2021 ) ACE1 Not mentioned European, Mediterranean, and the Middle East Not mentioned ACE D/I polymorphism was associated with increased COVID-19-related death.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… ( Gunal et al, 2021 ) ACE rs4341, rs4343 Spain 128 COVID-19 patients rs4341 and rs4343 were associated with more severe SARS-CoV-2 disease in patients with hypertension and diabetes. ( Íñiguez et al, 2021 ) ACE, ACE2 rs2106809,rs2285666 Turkey 155 COVID-19 patients No association was observed with the severity of SARS-CoV-2 infection. ( Karakaş Çelik et al, 2021 ) ACE1 Not mentioned European, Mediterranean, and the Middle East Not mentioned ACE D/I polymorphism was associated with increased COVID-19-related death.…”
Section: Discussionmentioning
confidence: 96%
“…Our review found that ACE-1 single nucleotide polymorphisms (SNP) rs4341 and rs4343 were linked to severe infection in hypertensive, dyslipidemic, and type 2 diabetic patients. rs2074192 ( ACE-2 ) and rs1799752 ( ACE-1 ) variants, and rs699 ( AGT ) SNP were also hypothesized to predict the clinical outcome of patients infected with SARS-CoV-2 ( Cafiero et al, 2021 , Íñiguez et al, 2021 ). However, we found just one study assessing the rs1799752 polymorphism of ACE-1 receptor which showed no association with ICU admission of severe COVID-19 patients ( Baştuğ et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The limited understanding of biological mechanisms and the impact of host genetic risk factors on severe COVID-19 has led researchers to identify genetic risk variants and analyze their influence on the development of severe symptoms. Our study is analogous to the molecular network analysis studies of protein interactions derived from risk variants identified from GWAS and statistical summaries conducted among different populations [3,9,29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ACE2 counterbalances Ang II–AT1R effects by either stimulating an alternative pathway for Ang I degradation to produce Ang-(1–9), or by inactivating Ang II and hydrolyzing it to a heptapeptide Ang-(1–7). The latter stimulates vasodilation and activates anti-inflammatory, antifibrotic, and antithrombotic cascades via the MasR axis [ 59 , 60 ], as well as the protection of endothelial cell activity [ 57 , 58 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%